The role of walking and cycling in reducing the impacts of climate change - Pooley, C; Horton, D; Scheldeman, G; Tight, M; Harwatt, H; Jopson, A; Jones, T; Chisholm, A; Mullen, C (Emerald Group Publishing Limited, 2012)
Purpose – To examine the potential for switching short trips in urban areas from cars to walking and cycling, and the possible contribution, this could make to a reduction in transport-related greenhouse gas emissions. Methods – Case studies in four urban areas combining a questionnaire survey, interviews with households and during journeys and in-depth ethnographies of everyday travel. Findings – The barriers to an increase in walking and cycling in British urban areas are emphasised. It demonstrates that motivations for walking and cycling are mostly personal (health and local environment) and that the complexities and contingencies of everyday travel for many households, combined with inadequate infrastructure, safety concerns and the fact that walking and cycling are seen by many as abnormal modes of travel, mean that increasing rates of walking and cycling will be hard. Given that the contribution of trips less than 2 miles to transport-related greenhouse gas emissions is relatively small, it is argued that any gains from increased walking and cycling would mostly accrue to personal health and the local environment rather than to the UK's carbon reduction target. Social implications – Positive attitudes towards walking and cycling are motivated mainly by personal concerns rather than global environmental issues. Originality – Use of detailed ethnographic material in policy-related transport research.